The Calcium-Induced Regulation in the Molecular and Transcriptional Circuitry of Human Inflammatory Response and Autoimmunity - de Seabra Rodrigues Dias, Ivo R.; Mok, Simon W. F.; Gordillo-Martínez, Flora; Khan, Imran; Hsiao, Wendy W. L.; Law, Betty Y. K.; Wong, Vincent K. W.; Liu, Liang (Frontiers in Pharmacology, 2018)
Rheumatoid arthritis synovial fibroblasts (RASFs) are fundamental effector cells in RA driving the joint inflammation and deformities. Celastrol is a natural compound that exhibits a potent anti-arthritic effect promoting endoplasmic reticulum (ER) stress mediated by intracellular calcium (Ca2+) mobilization. Ca2+ is a second messenger regulating a variety of cellular processes. We hypothesized that the compound, celastrol, affecting cytosolic Ca2+ mobilization could serve as a novel strategy to combat RA. To address this issue, celastrol was used as a molecular tool to assay the inflammatory gene expression profile regulated by Ca2+. We confirmed that celastrol treatment mobilized cytosolic Ca2+ in patient-derived RASFs. It was found that 23 genes out of 370 were manipulated by Ca2+ mobilization using an inflammatory and autoimmunity PCR array following independent quantitative PCR validation. Most of the identified genes were downregulated and categorized into five groups corresponding to their cellular responses participating in RA pathogenesis. Accordingly, a signaling network map demonstrating the possible molecular circuitry connecting the functions of the products of these genes was generated based on literature review. In addition, a bioinformatics analysis revealed that celastrol-induced Ca2+ mobilization gene expression profile showed a novel mode of action compared with three FDA-approved rheumatic drugs (methotrexate, rituximab and tocilizumab). To the best of our knowledge, this is a pioneer work charting the Ca2+ signaling network on the regulation of RA-associated inflammatory gene expression.